The Surface of Public Space. Working with the â€œPlaneâ€ to Design Urban Voids (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
This Paper examines the â€œreturn to the surfaceâ€ in the design of contemporary urban space: shunned by modernist thinking, this dimension has now reacquired importance and ... â€œreliefâ€. The surface, horizontal and vertical, is no longer a space of capricious decoration. Landscaping, texture, colour, tactile, visual and audio effects are now structuring materials. They configure weak actions with strong effects. The soil, in particular, is the â€œskinâ€ of public space, its face. Promenades, piazzas, widenings, crossroads, grow more complex in their performance and image, intensifying the experience of their use. They indicate specific functions, through a design of palimpsests.They draw lines on the ground for team sports, trace maps for the installationÂ of furnishings, host technological networks, bring light and air to underground spaces and incorporate lighting. Like faÃ§ades, soils also multiply their layering to become complex technological and bioclimatic devices. For example, ventilated walls and â€œdry laidâ€ paving. Or vertical screens, brise-soleil and silkscreened walls, rises and drops, undulations and level changes, technical floors, raised paving, plug-in grids, landscaped parterres: from the second screen to ... the second pavement!This text describes techniques, morphological developments and feasibility and offers an excursus through examples from past and recent history.